VIAGENS LITERÁRIAS: LITERARY TRIPS - Viola, Alan Flávio (Episteme Transversalis, 2018)
Viagens literárias é um texto montado por citações de vários escritores a partir de uma narrativa que as une – como a literatura lê o mundo e seus movimentos, as viagens. Procurei trazer a diferença das dicções dos autores, e a grandiosidade no domínio da ficção nessa minha pesquisa. Há também uma consagração das traduções nesse trabalho, todas de excelência. Abstract “Literary Journeys” is a text assembled by quotes from various writers from a narrative that unites them - as literature reads the world and its movements, journeys. I tried to bring the difference of the authors' dictions, and the grandeur in the realm of fiction in my research. There is also a consecration of the translations in this work, all of excellence.